The ANALISIS KINERJA COLD PAVING HOT MIX ASBUTON DENGAN FILLER PORTLAND CEMENT TERHADAP INTENSITAS RENDAMAN - Andri Irfan Rifai; Muhammad Hafidh; Muhammad Isradi; Joewono Prasetijo (TEKNISIA, 2023)
Using Cold Paving Hot Mix Asbuton (CPHMA) is an alternative to road preservation needs in the form of quick patching in Indonesia, which is considered optimal. However, until now, CPHMA still needs to be considered strong against natural challenges with high rainfall. This paper aims to test the performance of CPHMA with Portland cement filler against the Immersion Test. The immersion test is a laboratory model as an approach to immersion due to rainfall on road preservation. The test specimens were selected based on the optimum asphalt content, comprising 57 pieces. Tests are carried out in the laboratory with various Indonesian National Standard tests. Then the Marshall test was carried out with standard conditions (2x75 collisions) to determine density, stability, yield, Marshall quotient, standard durability tests, and modified durability to determine the durability index value. The Immersion test results showed that CPHMA with 1% Portland cement as filler and optimum asphalt content of 6% could withstand immersion for three days, 7 hours, 37 minutes 15 seconds. The duration of the immersion is relatively long compared to the period of immersion in the field due to the rain that occurred.